English Edugame Application for Childhood base on Android - Dony Novaliendry; Sisca Andriani (Ikatan Ahli Informatika Indonesia (IAII), 2020)
apply arithmetic with play compared to without playing. Play and child is an inseparable unity. Play activities carried out children and children’s activities always indicate play activities. In childhood the comprehension is very high, more activities a child does, the ability to remember will also be higher. There are several factors make it difficult for children to recite and remember the object, color around them, it is less interested in the media used. Childhood always follows the rhyme of its development. at an early age, language development is very important, because at this age it is a sensitive period for children. The English language is the International language. English language for children starts from introducing vocabulary that is closest to the child, the goals to make it easier for children to remember. One way to maximal comprehension by giving learning fun involves learning with the game. The research resulted in an English game application based on android. In this application, there are education and game features. The education features an exciting good and gets the sound from the lesson that is available. Game features available are guessed pictures, guess sounds, and puzzles. The purpose of English edugame application to teach children vocabulary of English and make children not bored to learn.